UPAYA MENINGKATKAN KEMAMPUAN MENULIS LAPORAN PENGAMATAN DALAM PELAJARAN BAHASA INDONESIA MELALUI PEMBELAJARAN KONTEKSTUAL BAGI SISWA KELAS V SDN 5 SUKAWARGI - Ihah Solihah; Euis Siti Mauludiah; Imas Mulyaningsih (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This study aims to determine (1) students' writing skills before using contextual learning models, (2) students' writing abilities after using contextual learning models, (3) student responses in using contextual learning models. This type of research is Classroom Action Research (CAR) with research subjects in class V SDN 5 Sukawargi consisting of 20 students. Based on the results of the study it can be concluded that. (1) students' writing skills before using the contextual learning model, that is, 3 students who complete or with a percentage of 15%. (2) students' writing abilities after using the contextual learning model, namely in the first cycle of students who completed 9 people or with a percentage of 45%. Furthermore, in cycle II, 16 students who passed or a percentage of 80% completed. To be more convincing, 20 students complete the third cycle with a percentage of 100%. This shows that the ability of students in writing observation reports has reached a classical level of 100% completeness learning. (3) student responses using contextual learning models in learning Indonesian are positive. Thus that using contextual learning models can improve students' ability to write observation reports.